Bone healing at non-submerged implants installed with different insertion torques: a split-mouth histomorphometric randomized controlled trial - Yoshiyuki Amari; Adriano Piattelli; Karol Alí Apaza Alccayhuaman; Natalia Fortich Mesa; Mauro Ferri; Giovanna Iezzi; Daniele Botticelli (SpringerOpen, 2019)
Abstract Objectives To evaluate histomorphometrically the healing at implants installed with standard or very low insertion torque values Material and methods Twelve volunteer patients were recruited, and two screw-shaped titanium devices were installed in the distal segments of the mandible using insertion torque values of either < 10 Ncm or ~ 30 Ncm. The implants were left to heal in a non-submerged fashion. After 8 weeks, biopsies were retrieved, and ground sections were prepared for histological evaluation. Results Histological slides from 11 patients were available for (n = 11). The new bone in contact with the implant surface was 39.3 ± 18.5% and 49.4 ± 9.4% at the < 10 and ~ 30 Ncm sites, respectively. Considering the pre-existing old bone, the total mineralized bone was 46.8 ± 22.1% at the < 10 Ncm sites and 57.0 ± 14.1% at the ~ 30 Ncm. No statistically significant differences were found. New bone density and total mineralized bone density were 36.6 ± 8.1% and 53.0 ± 13.5% at the < 10 Ncm sites and 35.9 ± 10.0% and 52.2 ± 16.0% at the ~ 30 Ncm sites, respectively. No statistically significant differences were disclosed. Conclusion From the data of the present study, it can be concluded that a trend of higher osseointegration was observed at the ~ 30 Ncm compared to the < 10 Ncm torque group. Nevertheless, it can be concluded that an implant installed with a very low torque may achieve a good integration. Trial registration ClinicalTrials.gov  NCT04017156; trial retrospectively registered on 12 July 2019.